A climate change modelling framework for financial stress testing in Southern Africa - Anvari, Vafa; Arndt, Channing; Hartley, Faaiqa; Makrelov, Konstantin; Strezepek, Kenneth; Thomas, Timothy S.; Gabriel, Sherwin; Merven, Bruno (South African Reserve Bank, 2022)
Central banks play a critical role in the economy, with policy levers that influence and are influenced by climate change. An important part of central bank interventions is conducting climate-related stress tests and scenario analysis to increase awareness in the financial sector of the effects of climate change, improve the integration of climate-related risks into financial companies’ decisions, identify important data gaps, and start building capacity to develop more advanced and accurate climate scenarios. These exercises, however, are a challenge to central banks and financial companies because of their complexity and the new data and tools required for scenario development and analysis. The development of scenarios for climate-related stress testing requires the integration of different model frameworks to assess the impacts of climate change, translate these impacts into macroeconomic scenarios, and evaluate the subsequent financial sector outcomes. This integration requires multidisciplinary skills such as the joint work of energy system modellers, climate scientists and macroprudential experts. This paper provides an overview of the modelling frameworks available for assessing climate change impacts in South Africa, covering both local and global models. This should assist financial institutions and regulators with developing partnerships to build scenarios and assess the impact of climate-related risks. Gaps in current models and modelling for financial stress testing are also identified as considerations for future research.